Cost effectiveness of strategies to combat cardiovascular disease, diabetes, and tobacco use in sub-Saharan Africa and South East Asia: mathematical modelling study. (2012)
To determine the relative costs and health effects of interventions to combat cardiovascular disease, diabetes, and tobacco related disease in order to guide the allocation of resources in developing countries. Cost effectiveness analysis of 123 single or combined prevention and treatment strategies for cardiovascular disease, diabetes, and smoking by means of a lifetime population model. Two World Health Organization sub-regions of the world: countries in sub-Saharan Africa with very high adult and high child mortality (AfrE) and countries in South East Asia with high adult and high child mortality (SearD). Demographic and epidemiological data were taken from the WHO databases of mortality and global burden of disease. Estimates of intervention coverage, effectiveness, and resource needs were drawn from clinical trials, observational studies, and treatment guidelines. Unit costs were taken from the WHO-CHOICE (Choosing Interventions that are Cost-Effective) price database. Cost per disability adjusted life year (DALY) averted, expressed in international dollars ($Int) for the year 2005. Most of the interventions studied were considered highly cost effective, meaning they generate one healthy year of life at a cost of less than $Int2000 (which is the gross domestic product per capita of the two regions considered here). Interventions that offer particularly good monetary value, and which could be considered for prioritised implementation or scale up, include demand reduction strategies of the Framework Convention for Tobacco Control ( less than $Int950 and less than $Int200 per DALY averted in AfrE and SearD respectively); combination drug therapy for people with a >25% chance of experiencing a cardiovascular event over the next decade, either alone or together with specific multidrug regimens for the secondary prevention of post-acute ischaemic heart disease and stroke ( less than $Int150 and less than $Int230 per DALY averted in AfrE and SearD respectively); and retinopathy screening and glycaemic control for patients with diabetes ( less than $Int2100 and less than $Int950 per DALY averted in AfrE and SearD respectively). This comparative economic assessment has identified a set of population-wide and individual strategies for prevention and control of cardiovascular disease that are inexpensive and cost effective in low resource settings.